Improving Pantun Writing Skills Using Picture Media (Classroom Action Research On Fourth Grade Elementary School Students) : - Nazri, Fahri; Chandra, Deni; Pratama, Febri Fajar (CV. Generasi Insan Rafflesia, 2025)
This study aims to improve the pantun writing skills of fourth-grade students at SDN Empang in the 2024/2025 academic year through the use of visual media. The background of this study stems from the low ability of students in writing pantun due to conventional learning methods, which are predominantly lecture-based and lack supporting media. This study used the Classroom Action Research (CAR) method developed by Kemmis and McTaggart, which was carried out in two cycles, each consisting of the planning, action, observation, and reflection stages. The research subjects were 12 fourth-grade students, consisting of 7 male students and 5 female students. The research instruments were a pantun writing test and observation sheets for teacher and student activities. The results showed a significant improvement in pantun writing skills. The pre-action average score of 54.94% increased to 72.65% in cycle I and reached 91.87% in cycle II. This improvement was supported by the active involvement of students in observing pictures, discussing, and expressing creative ideas in the form of pantun. Thus, the use of visual media proved to be effective in increasing student motivation, creativity, and learning outcomes in writing pantun. This study recommends that teachers optimize visual media as an innovative learning strategy in elementary schools.